Changes in susceptibility of Plasmodium falciparum to antimalarial drugs in Uganda over time: 2019–2024 - Martin Okitwi; Stephen Orena; Patrick K. Tumwebaze; Thomas Katairo; Yoweri Taremwa; Oswald Byaruhanga; Stephen Tukwasibwe; Samuel L. Nsobya; Jennifer Legac; Jeffrey A. Bailey; Roland A. Cooper; Melissa D. Conrad; et al. (Nature Communications)
Abstract The treatment and control of malaria in Africa is challenged by drug resistance. We characterized ex vivo susceptibilities to nine drugs of isolates collected from individuals presenting with uncomplicated falciparum malaria in eastern (2019-2024) and northern (2021-2024) Uganda and performed deep sequencing, with analysis of 80 Plasmodium falciparum genes, to evaluate associations between susceptibilities and potential resistance markers for samples studied since 2016. For 1114 evaluated isolates, median half-maximal inhibitory concentrations (IC50s) were low-nanomolar for chloroquine, monodesethylamodiaquine, piperaquine, pyronaridine, lumefantrine, mefloquine, and DHA, but higher for quinine and pyrimethamine. Over time, susceptibilities improved for chloroquine, decreased for lumefantrine, mefloquine, and DHA, and were unchanged for other drugs. Changes in prevalences of known markers of altered drug susceptibility followed the same patterns. Genotypes associated with drug susceptibility were those previously identified for aminoquinolines and pyrimethamine. For lumefantrine, susceptibility was decreased with wild-type PfCRT K76T or PfMDR1 N86Y, mutant PfK13 C469Y or A675V, mutant PfCARL D611N, and other polymorphisms. For DHA, susceptibility was decreased with the PfK13 C469Y or A675V and PfMDR1 Y500N mutations. Decreasing activities of lumefantrine and DHA suggest potential loss of efficacies of leading regimens, although the clinical consequences of these changes are, to date, uncertain.